2020
DOI: 10.1097/iae.0000000000002853
|View full text |Cite
|
Sign up to set email alerts
|

Perfluorocarbon Liquid–assisted Inverted Internal Limiting Membrane Flap Technique Versus Internal Limiting Membrane Peeling for Highly Myopic Macular Hole Retinal Detachment

Abstract: Purpose: To compare the efficacy of a modified perfluorocarbon liquid–assisted inverted internal limiting membrane (ILM) flap technique with the standard ILM peeling for the treatment of macular hole retinal detachment in highly myopic eyes. Methods: This was a retrospective, consecutive, nonrandomized comparative study. Forty-two macular hole retinal detachment eyes of 42 patients were included into either a perfluorocarbon liquid–assisted inverted ILM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…The ILM peeling technique effectively reattached the retina but failed to achieve a satisfactory MH closure rate ( 7 12 ). Instead, the inverted ILM flap technique reached favorable anatomic results ( 8 , 11 – 13 ). However, previous studies of the effect of these two techniques on the postoperative BCVA have shown inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ILM peeling technique effectively reattached the retina but failed to achieve a satisfactory MH closure rate ( 7 12 ). Instead, the inverted ILM flap technique reached favorable anatomic results ( 8 , 11 – 13 ). However, previous studies of the effect of these two techniques on the postoperative BCVA have shown inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…Although the retinal reattachment rate is high after the conventional pars plana vitrectomy (PPV) technique with membrane complex removal, the MH closure rate has been unsatisfactory, ranging from 25 to 86% ( 7 12 ). After introducing the inverted ILM flap technique, better anatomical success was achieved in recent years ( 8 , 11 – 13 ). Previous studies have demonstrated that the inverted flap technique assisted by perfluorocarbon liquid (PFCL) can achieve a better functional and anatomical prognosis ( 8 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 85 The use of perfluorocarbon liquid in FTMHs with RD and viscoat ® in FTMHs without RD combined with inverted ILM flap technique were proposed to increase the success rate of the surgery. 86 , 87 …”
Section: Surgical Outcomes Of Inverted Ilm Flap Techniquementioning
confidence: 99%
“…85 The use of perfluorocarbon liquid in FTMHs with RD and viscoat ® in FTMHs without RD combined with inverted ILM flap technique were proposed to increase the success rate of the surgery. 86,87 Comparing with idiopathic FTMHs, traumatic FTMHs have a higher likelihood of spontaneous closure (up to 67%) that often occurs within 3 months after ocular trauma. 88 There was a trend toward small size in spontaneously closed traumatic FTMHs.…”
Section: Secondary Ftmhmentioning
confidence: 99%